Hubungan Konsumsi Kopi Dengan Kadar Asam Urat, Kolestrol, dan Body Mass Index (BMI) di Warkop Asli Medan - Ananda, Rayhan Khozin Aulia; Lubis, Yolanda Eliza Putri; Suandy, Suandy (Syntax Corporation, 2025)
Coffee consumption has become part of people's lifestyle, especially among the productive age group. Coffee contains active compounds known to affect purine metabolism, lipid profile, and nutritional status. This study aims to analyze the relationship between coffee consumption and uric acid levels, cholesterol, and Body Mass Index (BMI) among consumers at Warkop Asli Medan. This study employed a descriptive observational design with a cross-sectional approach conducted from May to August 2025. A total of 96 respondents were selected using purposive sampling technique. Data were collected through questionnaires and direct examinations including uric acid levels, cholesterol, and BMI measurements. Data analysis used chi-square test with significance level of α = 0.05. The majority of respondents were male (65.6%) with moderate coffee consumption (59.4%). Examination results showed 81.3% of respondents had normal uric acid levels, 76.0% had normal cholesterol levels, and 60.4% had normal BMI. Bivariate analysis showed no significant relationship between coffee consumption and uric acid levels (p=0.426), BMI (p=0.160), and cholesterol (p=0.905). There is no significant relationship between coffee consumption and uric acid levels, cholesterol, and BMI among consumers at Warkop Asli Medan.